2021
DOI: 10.3390/ijms22052754
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thioredoxin-Interacting Protein in Diseases and Its Therapeutic Outlook

Abstract: Thioredoxin-interacting protein (TXNIP), widely known as thioredoxin-binding protein 2 (TBP2), is a major binding mediator in the thioredoxin (TXN) antioxidant system, which involves a reduction-oxidation (redox) signaling complex and is pivotal for the pathophysiology of some diseases. TXNIP increases reactive oxygen species production and oxidative stress and thereby contributes to apoptosis. Recent studies indicate an evolving role of TXNIP in the pathogenesis of complex diseases such as metabolic disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 185 publications
1
53
0
Order By: Relevance
“…Independent CpGs included were cg00574958 from carnitine palmitoyl transferase 1A ( CPT1A) , cg02650017 from Phosphoethanolamine/Phosphocholine Phosphatase 1 ( PHOSPHO1 ), cg06500161 from ATP Binding Cassette Subfamily G Member 1 ( ABCG1 ), cg11024682 from Sterol Regulatory Element Binding Transcription Factor 1 ( SREBF1 ), cg18181703 from Suppressor Of Cytokine Signaling 3 ( SOCS3 ), and cg19693031 from Thioredoxin Interacting Protein ( TXNIP ). Bolstering to the validity of our CpG selection each gene has strong biological plausibility for association with MetS including roles in fatty acid metabolism ( CPT1A ) [ 17 ], lipid homeostasis and metabolism ( SREBF1 [ 18 ], ABCG1 ) [ 19 ], skeletal endocrine regulation of metabolism ( PHOSPHO1 ) [ 20 ], cytokine signaling (SOCS3) [ 21 ] and oxidative stress ( TXNIP ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Independent CpGs included were cg00574958 from carnitine palmitoyl transferase 1A ( CPT1A) , cg02650017 from Phosphoethanolamine/Phosphocholine Phosphatase 1 ( PHOSPHO1 ), cg06500161 from ATP Binding Cassette Subfamily G Member 1 ( ABCG1 ), cg11024682 from Sterol Regulatory Element Binding Transcription Factor 1 ( SREBF1 ), cg18181703 from Suppressor Of Cytokine Signaling 3 ( SOCS3 ), and cg19693031 from Thioredoxin Interacting Protein ( TXNIP ). Bolstering to the validity of our CpG selection each gene has strong biological plausibility for association with MetS including roles in fatty acid metabolism ( CPT1A ) [ 17 ], lipid homeostasis and metabolism ( SREBF1 [ 18 ], ABCG1 ) [ 19 ], skeletal endocrine regulation of metabolism ( PHOSPHO1 ) [ 20 ], cytokine signaling (SOCS3) [ 21 ] and oxidative stress ( TXNIP ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…TXNIP has attracted considerable attention regarding drug development owing to its multiple functions and involvement in metabolic disorders, inflammation, neurodegenerative disorders as well as cancer ( Qayyum et al, 2021 ). Generally, TXNIP is considered as a vital regulator in response to oxidative stress relying on interacting with reduced thioredoxin (Trx),and further blocking its potential for scavenging reactive oxygen species ( Alhawiti et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous evidence further revealed that TXNIP elicited bone loss by promoting the excessive mitochondrial oxidative phosphorylation under conditions of oxidative stress induced by GC, which can be blocked in the TXNIP knockout mice ( Mo et al, 2021 ). Several preclinical and clinical evidence related to diabetes mellitus supported the TXNIP-specific inhibitors for the development of new promising agents ( Qayyum et al, 2021 ), such as Verapamil ( Khodneva et al, 2016 ), Taurine ( Gondo et al, 2012 ), and SRI-37330 ( Thielen et al, 2020 ). It was reported that TXNIP pathway could be inhibited by a salvianolate injection ( Qiu et al, 2018 ), the main water-soluble bioactive compounds of Salvia miltiorrhiza bunge.…”
Section: Discussionmentioning
confidence: 99%
“…TXNIP increases reactive oxygen species production by binding with thioredoxin. TXNIP is upregulated in diabetes, cardiovascular disease, and neurodegerative disorders [81]. PTN expression can be triggered in tissues by many factors including inflammation and mechanical stress [82].…”
Section: Discussionmentioning
confidence: 99%